Impact of integrated graphical display on expert and novice diagnostic performance in critical care. (17th June 2020) - Reese, Thomas J; Del Fiol, Guilherme; Tonna, Joseph E; Kawamoto, Kensaku; Segall, Noa; Weir, Charlene; Macpherson, Brekk C; Kukhareva, Polina; Wright, Melanie C
Abstract: Objective: To determine the impact of a graphical information display on diagnosing circulatory shock. Materials and Methods: This was an experimental study comparing integrated and conventional information displays. Participants were intensivists or critical care fellows (experts) and first-year medical residents (novices). Results: The integrated display was associated with higher performance (87% vs 82%; P < .001), less time (2.9 vs 3.5 min; P = .008), and more accurate etiology (67% vs 54%; P = .048) compared to the conventional display. When stratified by experience, novice physicians using the integrated display had higher performance (86% vs 69%; P < .001), less time (2.9 vs 3.7 min; P = .03), and more accurate etiology (65% vs 42%; P = .02); expert physicians using the integrated display had nonsignificantly improved performance (87% vs 82%; P = .09), time (2.9 vs 3.3; P = .28), and etiology (69% vs 67%; P = .81). Discussion: The integrated display appeared to support efficient information processing, which resulted in more rapid and accurate circulatory shock diagnosis. Evidence more strongly supported a difference for novices, suggesting that graphical displays may help reduce expert–novice performance gaps.